2006
DOI: 10.1111/j.1469-1795.2006.00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of trophy hunting to create incentives for wildlife conservation in Africa where alternative wildlife‐based land uses may not be viable

Abstract: There is a lack of consensus among conservationists as to whether trophy hunting represents a legitimate conservation tool in Africa. Hunting advocates stress that trophy hunting can create incentives for conservation where ecotourism is not possible. We assessed the hunting preferences of hunting clients who have hunted or plan to hunt in Africa (n = 150), and the perception among African hunting operators (n = 127) of client preferences at two US hunting conventions to determine whether this assertion is jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
139
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(160 citation statements)
references
References 20 publications
(30 reference statements)
2
139
1
4
Order By: Relevance
“…In particular, farmers and hunters felt they were excluded from participation and involvement in carnivore management by central authorities (Ericsson & Heberlein 2003;Skogen 2003). In other parts of the world, Lindsey et al (2006) showed how local participation by trophy hunters in Africa contributed to wildlife conservation, while hunters in Wisconsin did not support wolf conservation in their area (Treves & Martin 2011;Bruskotter & Fulton 2012). In Scandinavia, hunters generally do not support the conservation of large carnivores (Ericsson & Heberlein 2003;Roskaft et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, farmers and hunters felt they were excluded from participation and involvement in carnivore management by central authorities (Ericsson & Heberlein 2003;Skogen 2003). In other parts of the world, Lindsey et al (2006) showed how local participation by trophy hunters in Africa contributed to wildlife conservation, while hunters in Wisconsin did not support wolf conservation in their area (Treves & Martin 2011;Bruskotter & Fulton 2012). In Scandinavia, hunters generally do not support the conservation of large carnivores (Ericsson & Heberlein 2003;Roskaft et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Effects on non-game species reported include illegal killing of predators (Thirgood et al 2000;Valkama et al 2005), reduction of their prey (Lozano et al 2007), modification of the animal behaviour (Casas et al 2009) and decreases in recruitment of trees dispersed by game species (Nunez-Iturri et al 2008). In contrast, relatively few studies have examined positive effects of hunting on wildlife and/or ecosystem conservation (but see Thirgood et al 2000;Baker 1997;Lindsey et al 2006Lindsey et al , 2007White et al 2008).…”
Section: Communicated By C Gortázarmentioning
confidence: 99%
“…While both activities clearly have conservation benefits, and are often argued in favour of because of these benefits (for discussion see Castley et al 2001;Van der Merwe & Saayman 2003;Lindsey et al 2006Lindsey et al , 2007, they may also have disadvantages. For example, in the case of Lion, a single hunt may fetch up to US$ 130 000 (Loveridge et al 2007), and it has been argued, on the basis of analyses and data from East Africa, that as long as males older than 5 -6 years old are hunted, population growth can be sustained (Whitman et al 2004).…”
Section: Exploitationmentioning
confidence: 99%